Acetylshikonin inhibits the migration and invasion of A375 cells by reversing EMT process via the PI3K/Akt/mTOR pathway. Issue 1 (1st January 2019) - Jiang, Shuang; Wang, Haotian; Guo, Yan; Liu, Zhi; Song, Wu
Abstract: Acetylshikonin has an inhibitory effect on various tumour cells, but its inhibitory effect and mechanism of action in melanoma have not been reported. In this study, effects of acetylshikonin on the migration and invasion of human melanoma A375 cells and their underlying mechanism were investigated. A375 cells were treated with 0, 2, 4 and 8 μmol/L acetylshikonin and the proliferation ability, apoptosis rate, apoptosis-related protein expressions, migration and invasion, epithelial-mesenchymal transition (EMT) process and the protein expressions of phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/Akt/mTOR) signalling pathway were detected. The results showed that compared with 0 μmol/L acetylshikonin, the proliferation of A375 cells decreased and the apoptotic rate increased significantly in 2, 4 and 8 μmol/L acetylshikonin groups; meanwhile, the scratch healing rate of A375 cells increased and the number of invasive cells in the acetylshikonin-treated groups decreased significantly. Furthermore, acetylshikonin could also elevate the protein expression of Bax and the mRNA levels of E-cadherin, but lower the protein expressions of Bcl-2, matrix metalloproteinase-2 (MMP-2), MMP-9, fibronectin (FN), p-PI3K, p-Akt and p-mTOR and the mRNA levels of vimentin and N-cadherin. These results suggest that acetylshikonin can inhibit the migration and invasion of A375 cells, which may be related to its inhibiting the activation of PI3K/Akt/mTOR pathway and reversing the process of EMT.